A functional polymorphism of microRNA-143 is associated with the risk of type 2 diabetes mellitus in the northern Chinese Han population - Kong, Dexian; Duan, Ya; Wang, Jinli; Liu, Yabin (Frontiers in Endocrinology, 2022)
Objective: To explore the association between two polymorphisms of microRNA-143 (miR-143) and the risk of type 2 diabetes mellitus (T2DM) in the northern Chinese Han population. Study Design: This case–control study involved 326 patients with T2DM and 342 healthy controls. Two genetic variants (rs4705342 and rs353292) of miR-143 were genotyped by the polymerase chain reaction/ligase detection reaction (PCR-LDR) method. The levels of miR-143 in the serum from 52 T2DM patients and 55 healthy subjects were investigated by quantitative real-time PCR (qRT–PCR). Results: The CC genotype frequency of rs4705342 was significantly higher in the T2DM patients than in the healthy controls (P = 0.012). After adjusting for sex, age, and body mass index, the rs4705342 CC genotype was also related to a significantly increased risk of T2DM compared with the TT genotype (adjusted OR: 1.87; 95% CI = 1.09-3.19; P = 0.022). Stratified analyses demonstrated that T2DM patients with the rs4705342 CC genotype had significantly higher levels of low-density lipoprotein cholesterol (LDL-C), fasting blood glucose (FBG), and glycated haemoglobin (HbA1C) than those carrying the rs4705342 TT genotype. The qRT–PCR results showed that the expression levels of miR-143 were significantly higher in the serum of cases than in the serum of controls (P < 0.001). Furthermore, the levels of miR-143 were significantly higher in the serum of T2DM patients carrying the rs4705342 CC genotype than in those carrying the TC and TT genotypes of rs4705342 (P = 0.005 and 0.003, respectively). Conclusion: The CC genotype of rs4705342 might be a risk factor for developing T2DM by increasing the expression of miRNA-143 in the northern Chinese Han population.